Spatio-temporal re-organization of replication foci accompanies replication domain consolidation during human pluripotent stem cell lineage specification. Issue 18 (16th September 2016) - Wilson, Korey A.; Elefanty, Andrew G.; Stanley, Edouard G.; Gilbert, David M.
ABSTRACT: Lineage specification of both mouse and human pluripotent stem cells (PSCs) is accompanied by spatial consolidation of chromosome domains and temporal consolidation of their replication timing. Replication timing and chromatin organization are both established during G1 phase at the timing decision point (TDP). Here, we have developed live cell imaging tools to track spatio-temporal replication domain consolidation during differentiation. First, we demonstrate that the fluorescence ubiquitination cell cycle indicator (Fucci) system is incapable of demarcating G1/S or G2/M cell cycle transitions. Instead, we employ a combination of fluorescent PCNA to monitor S phase progression, cytokinesis to demarcate mitosis, and fluorescent nucleotides to label early and late replication foci and track their 3D organization into sub-nuclear chromatin compartments throughout all cell cycle transitions. We find that, as human PSCs differentiate, the length of S phase devoted to replication of spatially clustered replication foci increases, coincident with global compartmentalization of domains into temporally clustered blocks of chromatin. Importantly, re-localization and anchorage of domains was completed prior to the onset of S phase, even in the context of an abbreviated PSC G1 phase. This approach can also be employed to investigate cell fate transitions in single PSCs, which could be seen to differentiate preferentially from G1 phase. Together, our results establish real-time, live-cell imaging methods for tracking cell cycle transitions during human PSC differentiation that can be applied to study chromosome domain consolidation and other aspects of lineage specification.